Dynamics of behaviour and habitat-use of black-and-white ruffed lemurs (Varecia variegata variegata) in a captive zoo environment - De Cai; Fidelma Butler; Paul.S. Giller; Declan O’Donovan; Ruth Mary O’Riordan (Applied Animal Behaviour Science, 2025)

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Current and future carbon stocks in coastal wetlands within the Great Barrier Reef catchments - Micheli Duarte de Paula Costa; Catherine E. Lovelock; Nathan J. Waltham; Mary Young; Maria F. Adame; Catherine V. Bryant; Don Butler; David Green; Michael A. Rasheed; Cristian Salinas; Oscar Serrano; Paul H. York; et al. (Global Change Biology, 2021)
Australia's Great Barrier Reef (GBR) catchments include some of the world's most intact coastal wetlands comprising diverse mangrove, seagrass and tidal marsh ecosystems. Although these ecosystems are highly efficient at storing carbon in marine sediments, their soil organic carbon (SOC) stocks and the potential changes resulting from climate impacts, including sea level rise are not well understood. For the first time, we estimated SOC stocks and their drivers within the range of coastal wetlands of GBR catchments using boosted regression trees (i.e. a machine learning approach and ensemble method for modelling the relationship between response and explanatory variables) and identified the potential changes in future stocks due to sea level rise. We found levels of SOC stocks of mangrove and seagrass meadows have different drivers, with climatic variables such as temperature, rainfall and solar radiation, showing significant contributions in accounting for variation in SOC stocks in mangroves. In contrast, soil type accounted for most of the variability in seagrass meadows. Total SOC stock in the GBR catchments, including mangroves, seagrass meadows and tidal marshes, is approximately 137 Tg C, which represents 9%–13% of Australia's total SOC stock while encompassing only 4%–6% of the total extent of Australian coastal wetlands. In a global context, this could represent 0.5%–1.4% of global SOC stock. Our study suggests that landward migration due to projected sea level rise has the potential to enhance carbon accumulation with total carbon gains between 0.16 and 0.46 Tg C and provides an opportunity for future restoration to enhance blue carbon.

Methods for Increasing Cooperation Rates for Surveys of Family Forest Owners - Brett J. Butler; Jaketon H. Hewes; Mary L. Tyrrell; Sarah M. Butler (Small-scale Forestry, 2017)

Active smoking and risk of Luminal and Basal-like breast cancer subtypes in the Carolina Breast Cancer Study - Eboneé N. Butler; Chiu-Kit Tse; Mary Elizabeth Bell; Kathleen Conway; Andrew F. Olshan; Melissa A. Troester (Cancer Causes & Control, 2016)

Changes in extreme temperature and precipitation in the Caribbean region, 1961–2010 - Tannecia S. Stephenson; Lucie A. Vincent; Theodore Allen; Cedric J. Van Meerbeeck; Natalie McLean; Thomas C. Peterson; Michael A. Taylor; Arlene P. Aaron‐Morrison; Thomas Auguste; Didier Bernard; Joffrey R. I. Boekhoudt; Rosalind C. Blenman; et al. (International Journal of Climatology, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

(2-Methoxyethoxy)acetic acid: a urinary biomarker of exposure for jet fuel JP-8 - Clayton B’Hymer; Patricia Mathias; Edward Krieg; Kenneth L. Cheever; Christine A. Toennis; John C. Clark; James S. Kesner; Roger L. Gibson; Mary Ann Butler (International Archives of Occupational and Environmental Health, 2012)

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Forest Policy / Biosecurity - Linda Heath; Clark Row; Robert Perschel; Douglas Boucher; Patricia Elias; Katherine Lininger; Calen May-Tobin; Earl Saxon; Steven Ruddell; Sally Collins; Sarah Ruddell; Mo Zhou; et al. (Journal of Forestry, 2011)
7Massive fires in Indonesian peatlands in the 1990s and in eastern Russian peatlands in 2002 and last year have highlighted the need to manage forests overlying peat deposits, as well as converted peat forests and open peatlands. Peat or peaty soils, contain 65% or more of partially decayed vegetation, can burn freely or underground. They cover some 10 percent of worldwide forests and contain 25 percent of all terrestrial carbon. Recent massive greenhouse gas (GHG) emissions from fires in forested peat and peatland in Indonesia and in Russia highlight the need for policies to reduce GHG emissions. We discuss major peatland areas and quantify their carbon stocks and potential GHG emissions. Trends show that year-to-year emissions are variable, with huge pulses that are a significant share of global GHG emissions. We group suggested policy options into three approaches. The first approach, which will reduce peat-related product demand, includes a) restricting peat, and products produced on cleared forested peatland, from being labeled or counted in GHG reduction achievements, as renewable (which palm oil currently is considered); b) developing full substitutes for horticultural peat (comprising about half mined peat use); and c) developing renewable power in countries still dependent on peat for power generation. These options reduce the rate of developing newly mined peat/forest areas. Options for a second approach, which treat already drained and cleared forested peatlands, are: d) restoring functioning peat ecosystems by closing drainage ditches, allowing natural rewetting, and “seeding” with peat vegetation fragments, e) requiring current peat operators to restore mined areas right after all peat is removed, and f) converting them to other land uses, despite the acidic conditions of mined peat bogs. These options sharply reduce risks of peat fires. Finally, a third group of policy options reduces ignition risks and limit fire spread: g) developing monitoring, suppression techniques, h) organizing local landowner protection groups and i) improving public fire organizations.

The FAP self-concept scale (adult form) - Mary Jane Esplen; Noreen Stuckless; Terri Berk; Kate Butler; Steve Gallinger (Familial Cancer, 2009)

Understanding and Reaching Family Forest Owners: Lessons from Social Marketing Research - Brett J. Butler; Mary Tyrrell; Geoff Feinberg; Scott VanManen; Larry Wiseman; Scott Wallinger (Journal of Forestry, 2007)
Social marketing—the use of commercial marketing techniques to effect positive social change—is a promising means by which to develop more effective and efficient outreach, policies, and services for family forest owners. A hierarchical, multivariate analysis based on landowners' attitudes reveals four groups of owners to whom programs can be tailored: woodland retreat, working the land, supplemental income, and ready to sell. A prime prospect analysis segmenting landowners according to their level of engagement and interest in land management can be used to improve the efficiency of program implementation. Landowners showing low levels of engagement but high levels of interest are of special interest because they are likely to be receptive to a social marketing message and therefore should be a priority target for any such efforts. Using the demographic profile of the average family forest owner, newspapers and television were identified as important means for mass communication.